The Production of Nata Colored by Monascus purpureus J1 Pigments as Functional Food - TRESNAWATI PURWADARIA; LISRINA GUNAWAN; AGUSTIN WYDIA GUNAWAN (Microbiology Indonesia, 2010)
Pigments from Monascus sp. may color nata. The mold also produces monacolin K that inhibits HMG-CoA reductase affecting the reduction of blood cholesterol. The aim of this study was to produce the colored nata containing monacolin K. The mold was isolated from commercial angkak. Potato sucrose (PS) and synthetic glucose (SG) media were used to ferment nata with Monascus purpureus J1. Fermentation of nata in PS medium produced red nata, while that in SG medium produced orange nata. The color of nata was similar to the color of supernatant. The optimum red production was obtained after five days of incubation, while the orange production increased until the 14th day. The color concentrations of the supernatant of PS medium containing nata (35.4 μg mL-1) were lower than those without nata (12.4 μg mL-1). The colors of nata looked darker than the color of the supernatant. The concentration of monacolin K in the red nata and the supernatant of PS medium were 0.6 μg mL-1 and 4.6 μg mL-1 respectively, while those in the orange nata and the supernatant of SG medium were 3.2 μg mL-1 and 14.6 μg mL-1 respectively. Dry matter biomass in the PS medium was lower than that in the SG medium. Even though the color of nata looked relatively stable, analyses of the nata water extract that showed a stable condition only occurred in freezing (-20OC) and soaking in buffer solution of pH 12; boiling, water washing, and soaking in a solution of pH 3 and 7 reduced the pigment concentration. Monacolin K concentration was not stable for every treatment, especially for water washing and freezing. Eventhough it was not stable, the boiling nata contained red pigments and monacolin K of 19.7 μg mL-1 and 0.1 μg mL-1 respectively, which can be served as functional food.